Irrigated fodder as the pillar of cattle products' supply chains in the South Mediterranean area: present situation and future prospects - Sraïri G.M.T. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Recent evolutions of livestock systems in the South Mediterranean area converge towards an intensification of production. Rangeland systems located in rain fed areas may not be sufficient to ensure the supply of animal proteins. As a consequence, increased efforts are needed to get more milk and meat from irrigated areas, which imply a steady output of high quality forage. The study of water uses by livestock in irrigation schemes requires a complex methodology, which has to take into account various functions of production: (i) from water volumes of different sources to fodder (quantity of biomass and its distribution throughout the seasons) and then (ii) from forage to cattle products (both milk and meat at the same time as farms are often not specialised). Moreover, climate change affects water availability and intense pressure on groundwater may put at risk many livestock systems. In this study, we take the example of the Tadla large scale irrigated scheme (105,000 ha) to present the issue of water productivity through cattle. Then, we discuss the future prospects of this topic, given the possibilities of on-farm intervention to achieve a “Livestock Revolution”: improving farms’ income with a sustainable use of the available water resources.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)